The Application of CIPP Model in the Value-added Evaluation of Physical Education Skills Teaching in Higher Vocational Colleges - Li, Zhiqiang (Pacific International Journal, 2025)
This study investigates the application of the CIPP (Context, Input, Process, Product) model in conducting value-added evaluation of physical education (PE) skills teaching in higher vocational colleges. Traditional outcome-based assessment models in vocational PE often fail to account for individual student growth and contextual differences, leading to limited pedagogical effectiveness. With the CIPP model, this research constructs a comprehensive, student-centered evaluation framework designed to capture dynamic learning progress and enhance instructional quality. The study explores five major aspects: relevance of the CIPP model to vocational PE evaluation, practical challenges in implementation, framework and indicator design, weight determination using analytic methods, and dynamic adjustment mechanisms. Data were collected through expert consultations, large-scale surveys, and longitudinal field applications across multiple institutions, ensuring empirical rigor. The results demonstrate that the CIPP-based evaluation system improves feedback precision, supports continuous teaching improvement, and aligns with the principles of scientific validity, systemic integration, operability, and adaptability. The study concludes that the CIPP model offers a theoretically sound and practically feasible framework for advancing value-added evaluation in PE teaching within the context of higher vocational education.